Steatosis as main determinant of portal hypertension through a restriction of hepatic sinusoidal area in a dietary rat nash model. (13th October 2020) - Barberá, Aurora; Raurell, Imma; García‐Lezana, Teresa; Torres‐Arauz, Manuel; Bravo, Miren; Hide, Diana; Gil, Mar; Salcedo, María Teresa; Genescà, Joan; Martell, María; Augustin, Salvador
Abstract: Background & Aims: Portal hypertension (PH) can be present in pre‐cirrhotic stages, even in absence of fibrosis in non‐alcoholic steatohepatitis (NASH) patients. Liver endothelial dysfunction (ED) has been shown as responsible for this effect in short‐term dietary animal models. We evaluated the persistence of PH and underlying mechanisms in a long‐term rat model of NASH. Methods: Sprague‐Dawley rats were fed 8 or 36 weeks with control diet or high‐fat high‐glucose/fructose diet. Metabolic parameters, histology, ED and haemodynamics were characterized. Structural characteristics of liver sections were analysed using image analysis. Results: Both interventions reproduced NASH histological hallmarks (with steatosis being particularly increased at 36 weeks), but neither induced fibrosis. The 36‐week intervention induced a significant increase in portal pressure (PP) compared to controls (12.1 vs 8.7 mmHg, P  < .001) and the 8‐week model (10.7 mmHg, P  = .006), but all features of ED were normalized at 36 weeks. Image analysis revealed that the increased steatosis at 36‐week was associated to an increase in hepatocyte area and a significant decrease in the sinusoidal area, which was inversely correlated with PP. The analysis provided a critical sinusoidal area above which animals were protected from developing PH and below which sinusoidal flux was compromised and PP started to increase. Conclusion: Liver steatosis per se (in absence of fibrosis) can induce PH through a decrease in the sinusoidal area secondary to the increase in hepatocyte area in a long‐term diet‐induced rat model of NASH. Image analysis of the sinusoidal area might predict the presence of PH.